FINANCIAL TECHNOLOGY ADOPTION AND FINANCIAL PERFORMANCE: DIGITAL LITERACY MODERATION STUDY - Wati, Yenny; Bintari, Wisang Candra; Prayogo, Imam; Syahputri, Anggraini; Yusrizal, Yusrizal (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2025)
This study intends to evaluate how significant the effect of financial technology on the financial performance of commercial banking in the city of Pekanbaru, Indonesia, using digital literacy as a moderate variable. This study uses primary data from 200 respondents via a likert scale questionnaire. WarpPLS software was used for data analysis, which used partial least squares. The results of this study show that there is a substantial positive link between the use of financial technology and the financial performance of commercial banking. This favorable benefit, however, is more pronounced when digital literacy is high. Commercial banks with high levels of digital literacy can use financial technology more efficiently to improve their financial performance. These findings have substantial implications for policy development in the banking sector and promote enhanced digital literacy in society. This study is exclusive in that it investigates how financial technology affects the financial performance of commercial banks in Indonesia while considering the moderating role of digital literacy in the context of more rapid technological changes. These findings significantly contribute to the literature on developing countries, particularly Indonesia.